CURRICULUM DEVELOPMENT IN THE 21ST CENTURY: TRENDS AND CHALLENGES - Kalayo Hasibuan (Rahis Cendekia Indonesia, 2025)
This paper explores the evolving landscape of curriculum development in the 21st century, focusing on emerging global trends and the challenges that accompany them. As education systems respond to rapid technological advancement, globalization, and shifting labor market demands, curriculum frameworks are increasingly moving toward competency-based, student-centered, and technology-integrated models. The study employs a qualitative descriptive approach, including document analysis and expert interviews, to identify the key elements shaping modern curriculum design. Findings reveal that while there is significant progress in incorporating 21st-century skills, digital literacy, and global awareness into curricula, various barriers hinder effective implementation. These include insufficient teacher training, policy inconsistency, and the continued dominance of standardized testing. The paper concludes that successful curriculum reform requires a collaborative, inclusive, and context-sensitive approach that aligns educational policy, practice, and assessment with the evolving needs of learners and society.